Pronounced differences in visitation by potential pollinators to co-occurring species of Fabaceae in the Southwest Australian biodiversity hotspot. (23rd July 2020) - Scaccabarozzi, Daniela; Dixon, Kingsley W; Tomlinson, Sean; Milne, Lynne; Bohman, Björn; Phillips, Ryan D; Cozzolino, Salvatore
Abstract: Despite their diversity and the potential for specialized pollination systems, Australian Fabaceae have received little attention in pollination studies. In the Southwest Australian Floristic Region (SWAFR), a recognized biodiversity hotspot, co-occurring and abundant species of Faboideae exhibit a range of floral colours and forms, suggestive of adaptation to different groups of pollinators. For four communities of Fabaceae in the SWAFR we investigated whether co-occurring species overlap in pollinator genera, whether these pollinators show differences in behaviour on the pea flower and whether variations in stamen length and nectar composition among species are associated with different pollinator types. Species of Fabaceae were visited by one to four genera of native bees, suggesting varying levels of ecological specialisation. In Fabaceae with more specialized interactions, co-occurring species showed marked differences in the bee genera attracted. Unexpectedly, some Fabaceae frequently attracted beetles, which may play an important role in their pollination. There was no evidence for an association between stamen length or nectar composition and the type of pollinator. The introduced honeybee, visited all studied species of Fabaceae, suggesting that they may act both as a pollinator and a potential competitor with native pollinators.